2013
DOI: 10.1111/ppa.12115
|View full text |Cite
|
Sign up to set email alerts
|

Heritability ofUlmus minorresistance toDutch elm disease and its relationship to vessel size, but not to xylem vulnerability to drought

Abstract: Dutch elm disease (DED) is a vascular wilt disease that causes the occlusion and cavitation of xylem vessels. Therefore, it is hypothesized that those elms that are less vulnerable to cavitation by drought might be more resistant to DED. To test this hypothesis, the relationship between xylem vulnerability to cavitation and susceptibility to DED was examined in progenies of crosses between susceptible and resistant individuals of Ulmus minor. Hydraulic conductivity and xylem vulnerability curves were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 52 publications
4
55
1
1
Order By: Relevance
“…One of its medium-term priorities is to increase the genetic diversity of tolerant native elms. Elm tolerance to O. novo-ulmi has been shown to be inheritable (Townsend 2000, Solla et al 2014, Venturas et al 2014) and polygenic (quantitative) in nature (Aoun et al 2010). It also depends on constitutive and inducible mechanisms of defence (e.g., Martín et al 2007Martín et al , 2008bMartín et al , 2013.…”
Section: Resultsmentioning
confidence: 99%
“…One of its medium-term priorities is to increase the genetic diversity of tolerant native elms. Elm tolerance to O. novo-ulmi has been shown to be inheritable (Townsend 2000, Solla et al 2014, Venturas et al 2014) and polygenic (quantitative) in nature (Aoun et al 2010). It also depends on constitutive and inducible mechanisms of defence (e.g., Martín et al 2007Martín et al , 2008bMartín et al , 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Because tolerance to DED has been shown to be inheritable, progenies are likely to have similar tolerance to parent trees (Solla et al 2015;Venturas et al 2014). However, there is a risk of natural crossing with neighboring elms of lower tolerance, or with U. pumila.…”
Section: Testing Pilot Forest Restoration With Elmsmentioning
confidence: 99%
“…and Ulmus hybrids [142][143][144]. Susceptible trees had significantly wider and longer vessels than those that resisted the disease [144].…”
Section: Ecology and Epidemiologymentioning
confidence: 99%
“…Susceptible trees had significantly wider and longer vessels than those that resisted the disease [144]. Solla and Gil [142] hypothesized that vessel diameters and sap flow affected the dispersal of O. novo-ulmi in the elm host, and Venturas et al [144] suggested that xylem structure restricted the pathogen's spread in resistant elms.…”
Section: Ecology and Epidemiologymentioning
confidence: 99%